Optimizing Banking E-Service Excellence: A CSI and IPA Approach to Customer Satisfaction - Adrea Hanna Theresa; Teddy Chandra; Yusnita Octafilia; Mazzlida Mat Deli; Sarbaeni Sarbaeni (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
This study aims to assess the level of customer satisfaction at Bank BCA Harapan Raya Branch in Pekanbaru by analyzing the gap between customer expectations and their actual experiences. It also identifies which service criteria should be prioritized for improvement. The research employs the Customer Satisfaction Index (CSI) method to measure overall customer satisfaction and the Importance Performance Analysis (IPA) method to evaluate the importance and performance of each electronic service attribute, determining priority areas for improvement. The results show that 77.71% of customers at Bank BCA Harapan Raya Branch fall into the "Satisfied" category, indicating that most customers are generally pleased with the services provided. Attributes located in Quadrant II (service speed, service reliability, transaction security, and accessibility) should be maintained, while those in Quadrant I (ease of use, transaction security, and accessibility) require immediate improvement.